The Speculative Migrants of the Anthropocene. Human Flows in the Neoliberal Planet - Luisetti, Federico (Itinerari, 2023)
The human flows of the neoliberal planet are categorized according to a continuum of mobility forms and managed through framings that construct migration as a threat multiplier, a challenge to human security, and an opportunity to increase the “adaptive capacity” of vulnerable populations. This vision reflects the synthesis of good and bad circulation patterns, good and bad versions of the Anthropocene that characterizes the neoliberal Earth system worldview. The planet as a geochemical entity is a repository of environmental life-cycles that the stewards of the Anthropocene are committed to regulate. In the speculative logic of risk, environmental destruction and species salvation, desperate climate refugees and entrepreneurial climate migrants are two faces of the same coin.